Factsheet: West Sea Crisis In Korea - John McGlynn; Nan Kim (Japan Focus)
The factsheet that follows, prepared by Nan Kim in conjunction with members of the National Campaign to End the Korean War, provides an informative overview of the dangerous military standoff that has been unfolding on the Korean Peninsula ever since South Korea conducted a 4-hour artillery exercise on November 23. The exercise was conducted on Yeonpyeong Island, populated at the time by 1,000 South Korean soldiers and 1,300 civilians, about 12 kilometers from North Korea's coastline. The North, which several times asked the South to cancel the exercise prior to its start, and then called for a halt to the exercise when shells landed closer and closer to the North Korean coastline , responded with direct shelling of the island. This resulted in the killing of two South Korean soldiers and two civilian contractors working on a military base. (Pyongyang later expressed regret for the civilian deaths.). See CSPAN report here.An important detail in the factsheet reported in the Korean but apparently not the English press is that the volume of shelling conducted by the South reveals that this was no minor exercise. Information from South Korea's defense ministry reveals that the South "fired 3,657 times, or over 900 shells per hour," into waters near the Northern Limit Line (NLL).This factsheet was prepared by Nan Kim in conjunction with members of the National Campaign to End the Korean War. Nan Kim is assistant professor of history at the University of Wisconsin, Milwaukee and a specialist on modern Korean war memory.